EFFECT OF FERTILIZER TYPES ON YIELD AND QUALITY OF NAPIER (Pennisetum purpureum) GRASS ESTABLISHED IN MAKURDI AND HARVESTED AT DIFFERENT GROWTH STAGES DURING THE WET SEASON - Ikyume, Timothy Tertsegha; Shaahu, David T.; Enebi, Blessing; Tor-Anyyin, Doofan D.; Anzewu, Owlama E.; Opawoye, Fumilayo A.; Abba, Jerry J.; Ewetade, Rosemary O. (FUDMA JOURNAL OF SCIENCES, 2025)
Organic fertilizers may be alternatives to inorganic sources for improved pasture productivity. This research investigated the comparative performance of Pennisetum purpureum pasture as affected by use of organic and inorganic fertilizer types and sampled at different ages during the wet season. The study was a factorial experimental arrangement (4 x 3) laid out as split plot design with six replicates. The two factors were fertilizer type (control-no fertilizer, Urea, Poultry droppings and cow dung) and harvesting age (60, 90 and 120 days). Fertilizer application was at the rate of 300 kg/ha in two and three equal split applications for organic and urea fertilizers, respectively. Data collected were subjected to analysis of variance using SPSS version 23 at 5% probability level. Dry matter yield was not influenced (p>0.05) by all the factors in this experiment. Plant height increased (p<0.05) in pasture fertilized with urea compared to other organic fertilizers, while number of leaves and length reduced (p<0.05) in pasture fertilized with cattle manure only. Tiller diameter was higher (p<0.05) in pastures fertilized with urea compared to organic fertilizer. All chemical parameters measured were not affected (p>0.05) by the different sources of fertilizer used, but crude protein and ash content reduced (p<0.05) with increasing age, while crude fibre, nitrogen free extract, neutral detergent fibre and acid detergent fibre were increased (p<0.05) with increasing age of sampling. This study established that use of poultry droppings compared favourably with urea fertilizer and may be the alternative source of fertilizer for urea.